Conservation and revitalization of historic streets in China: Pingjiang Street, Suzhou. Issue 4 (4th July 2017) - Xie, Jing; Heath, Tim
Abstract: The late twentieth and early twenty-first century has witnessed the unfortunate plight of demolition or irreparable damage for thousands of historic streets across China as a result of urbanization and redevelopment. A core of committed practitioners, academics and enlightened local governments have begun to recognize the important historical legacy of these streets and are undertaking conservation and revitalization projects. In Suzhou, approximately 100 km west of Shanghai, Pingjiang Street/district is an historical urban area that has recently undergone sensitive conservation and become one of the 'must-see' places in the city. This paper presents a historical account of the development, demise and resurrection of the houses, streets and waterways of Pingjiang district. The area's long history can be broadly structured into two critical and dialectical phases: the period of growth and incremental change during the Imperial period, and the pressures for change and development during the twentieth century. The paper will compare the socio-cultural factors that have shaped the layout of houses, streets and waterways and thus the whole street/district during these contrasting periods. These periods of transition will be followed by a critical review and assessment of urban conservation and revitalization of the area under the banner of 'heritage'.